A novel approach of manual manipulation of the transnasal ileus tube for severe or recurrent benign adhesive small bowel obstruction - Li, Er-Sheng; Zhai, Yin-Jun; Han, Yin; Chang, Qian; Wang, Qi; Zhang, Hong-Yu (Frontiers in Surgery, 2025)
PurposeThis study seeks to evaluate the safety and efficacy of an innovative manual manipulation technique for the transnasal ileus tube in patients experiencing severe or recurrent adhesive small bowel obstruction (ASBO).Materials and MethodsPrior to the initiation of this research, approval was obtained from the institutional review board. The study was conducted within our institution, involving a cohort of fifty-four patients diagnosed with severe, multiple, or recurrent ASBO. These patients underwent treatment through active manipulation of the transnasal ileus tube, which entailed navigating obstructions by adjusting two balloons and resolving adhesions through the alternate advancement and retraction of the ileus tube. Angiographic outcomes were categorized as either complete or incomplete resolution of obstructions. Data were collected on technical success, initial and final angiographic outcomes, mortality, morbidity, and overall clinical outcomes. Follow-up assessments were conducted at 1, 3, 6, and 12 months, with annual evaluations thereafter.ResultsThe transnasal ileus tube was successfully placed in all patients without any procedure-related complications. The tube was successfully navigated and passed through obstructions to the cecum in 94.4% of cases, specifically in 51 out of 54 attempts. Follow-up angiograms, conducted over a period of 3–38 months, confirmed the unobstructed passage of contrast medium through the small bowel in 52 patients. Clinical follow-up data, with an average duration of 20 ± 11 months (95% CI: 17, 23 months; range, 6–45 months), were available for 52 patients. One patient died due to multiple organ failure, while the remaining 51 patients exhibited no clinical symptoms of small bowel obstruction.ConclusionThese preliminary findings indicate that manual manipulation of the transnasal ileus tube is non-surgical and therefore non-traumatic but nonetheless an effective method of internally lysing the adhesions with their double balloon technique and pulling the tube back and forth.